Vozes dissonantes em Vestido de noiva e Valsa nº6 de Nelson Rodrigues e a proposta de criação de um romance dramático - Soares, Priscila Luz Gontijo (2018)
The present work aims to investigate the presence of multiple voices in the theatrical works of Nelson Rodrigues, Vestido de novia and Valsa nº6, in dialogue with the writing of the novel O Homem Proibido (2007). The starting point of problematizing the sense of polyphony in the above mentioned Nelson Rodrigues’ texts is the contextualization of the literary career of the author, his literary influences and his experience in newspaper, where he worked in several areas demonstrating a polyphonic ability unparalleled to no other a Brazilian author and a determining factor for the construction of his aesthetic themes and obsessions. After this, we will undertake a shift of perspective between the concept of polyphonic novel developed by Mikhail Bakhtin and the reflection on the current dramatic form, inscribed in some entries, mapped by the Research Group on Drama of the University of Paris III, coordinated by Jean-Pierre Sarrazac, playwright, teacher and essayist on theater theory. In the lexicon of modern and contemporary drama, the French group suggests the extension of the concept of polyphony in line with other dramatic writing procedures: rhapsody, romanticization, monodrama (polyphonic), monologue, action and character crisis, the becoming, the voice and the theater of the possible. This research is in line with literary creation, which, although it does not exist formally, there are projects being carried out in the Program of Literature and Literary Criticism of PUC-SP. This study is guided from the point of view of literary creation, having as presupposition to welcome these multiple voices to analyze the construction of a delusional poetic prose. What procedures does Nelson Rodrigues use to create this explosion of voices in his dramatic texts, Vestido de Noiva and Valsa nº6, therefore becoming one of the greatest exponents of delirious poetics? What are the effects of the plurality of voices employed in such elaborations? The purpose of this study is to list written procedures where multiple voices are released. The writing of both the theoretical field and the fictional creation implies the creation of another time. The voice is due to the construction of poetic time, simultaneous actions, the crossing of temporalities and the vertigo of spacing. To make an analysis of how Nelson Rodrigues created such a foreign language and "dragged his tongue out of his customary furrows, causing it to be delirious," in Deleuze's words